Матеріали з досліджень дитинця Вишгорода 1972 р. - Блажевич, Н.В. (Археологія і давня історія України, 2010)
Статтю присвячено публікації матеріалів з розкопок дитинця давньоруського міста Вишгорода у
1972 р., де розкрито житлові та господарські будови
XII—XIII ст., а також гончарний горн кінця XVI—
XVII ст., раніше визначений В.В. Чумаченком домною або коптильної піччю давньоруського часу. В 1972 г. проводились раскопки на северо-восточной части детинца древнерусского города Вышгорода.
Исследованы котлованы жилища и хозяйственной постройки. Жилище, предположительно срубное, на подклете, отапливалось глинобитной печью с включением
плинфы. Границы котлована не определены.
Хозяйственная постройка столбовой конструкции.
Время существования построек — XII в.
Собрана большая коллекция материала XII—
XIII вв.: фрагменты кухонной и столовой посуды, амфор, стеклянных браслетов и посуды, изделия из черного и цветного металлов, шиферные пряслица. Кроме объектов древнерусского времени исследован гончарный горн XVI—XVII вв. In 1972, the excavations at the north-eastern part of
dytynets of Vyshgorod, an Ancient Rus period city, were
conducted. The foundation pits of a dwelling and a husbandry
structure were studied. The dwelling was presumably
a frame built on a basement; it was heated by a cob
stove built with plinthoi inclusions. The borders of a foundation
pit are not determined. Husbandry structure is of pillar construction.
Period of functioning of the buildings is referred to the
12th c. A big collection of the 12th and the 13th centuries material
has been obtained: fragments of kitchenware and
tableware, amphorae, glass bracelets and vessels, items
made of ferrous and non-ferrous metals, and shiver spindle
whorls. Besides the objects of Ancient Rus period, the 16th or
17th c. potter’s furnace has been studied.